Familial Aggregation for Ischemic Heart Disease - José Leandro Pérez Guerrero; William Arias Salazar (Revista Finlay)
Background: ischemic heart disease is a nosological entity of multifactorial origin with genetic predisposition and susceptible to environmental changes. Objective: to determine the existence of familial aggregation for ischemic heart disease in patients seen in the cardiology clinic at the Vladimir Ilich Lenin General Teaching Hospital in Holguín. Methods: an analytical observational study of cases and controls (family aggregation study) was carried out. The sample was made up of 60 new patients with a diagnosis of ischemic heart disease (cases) and another 60 patients without a diagnosis of coronary heart disease (controls), paired in a 1:1 ratio. The following variables were used: sex, age, family history of ischemic heart disease and environmental risk factors: smoking, hyperlipidemia, high blood pressure and sedentary lifestyle. The Chi square statistician was used by the Mantel-Haenszel method. The odds ratio (OR) was then calculated to determine the magnitude of association through the ratio of cross products. Results: in the case group there was a higher frequency in the family history for ischemic heart disease, being higher for first degree relatives with 31 relatives and 41.3 %. Hyperlipidemia was the most frequent risk factor with 36.7 % in the case group and 37.1 % in the control group. An approximately 4-fold increased risk of suffering from ischemic heart disease was determined in those individuals with a positive first-degree family history, while patients with hyperlipidemia have a 4.8 times greater risk of suffering from ischemic heart disease. Conclusions: there is family aggregation for ischemic heart disease and a higher risk of getting sick was shown in patients with a positive family history for the disease, mainly with first-degree relatives and with hyperlipidemia.